PENDAMPINGAN PEMASARAN PRODUK UKM ASRI JEWELLERY DALAM MENJAGA EKSISTENSINYA DI MASA PANDEMI COVID-19 - Ida Ayu Nyoman Yuliastuti; Putu Kepramareni; Anak Agung Putu Wiwik Sugiantari; I Ketut Sudipta Giri (UNHI Press, 2021)
Competition between MSMEs is getting tighter amidst the large number of workers or employees who have been dismissed until they are laid off, which causes competition to come from various parts, both domestic, regional and global. To be able to compete in the midst of the Covid-19 pandemic conditions, the right marketing strategy is needed to be able to maintain product sales from Asri Jewelery. So far, the marketing method of Asri Jewelery is still very simple, namely word of mouth for foreign tourists who have purchased products in its showrooms. To solve this problem, the community service team conducted observations, socialization, training and assistance in online marketing. Online marketing for Asri Jewelery products is carried out using Instagram, Facebook and selling through themarketplace. In carrying out this service activity, the participation of partners is very large in providing space and time to participate in all service activities carried out by the service team. From online marketing activities through Instagram, Facebook and this marketplace, the domestic market share of Asri Jewelery products is getting wider, so that Asri Jewelery can still maintain its business sustainability amid the current Covid-19 pandemic.